CIRI FONETIK BAHASA MINANGKABAU DI KECAMATAN SUNGAI PAGU KABUPATEN SOLOK SELATAN - Sari, Winda Rahma; Agustina, Agustina; Tamsin, Andria Catri (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACT This research is purposed to describe Minangkabau phonetic characteristics in Sungai Pagu district Solok Selatan regency. Phonetic characteristics described in this research were: (1) vocal, (2) consonant, (3) diphthong, (4) vocal distribution, (5) consonant distribution, and (6) diphthong distribution. The type of this research was qualitative research with descriptive method. Data for this research was words used by people in Sungai Pagu district. Minangkabau phonetic characteristics in Sungai Pagu district were: (1) there were 6 vocals, i.e. [i], [e], [ə], [a], [u], and [o], (2) there were 6 consonants, i.e. [p], [b], [t], [d], [k], [g], [?], [c], [j], [f], [s], [ɣ], [h], [r], [l], [m], [n], [ñ], [ƞ], [w], and [y], (3) there were 10 diphthong, i.e. [iu], [ia], [ua], [au], [ai], [ui], [ie], [ou], [əu], and [ue], (4) there were 5 vocal distributions could be used in all positions and 1 vocal distribution could not be used in all positions, (5) there were 8 consonant distributions could be used in front, middle, and end positions and 1 vocal distribution could not be used in all positions, and (6) there were 1 diphthong distributions could be used in all positions and 9 diphthong distribution used narrowly. Kata kunci: fonetik, vokal, konsonan, diftong, bahasa Minangkabau